Work and Health after Retirement: A Competing Risks Model with Semiparametric Unobserved Heterogeneity - Butler, J. S.; Anderson, Kathryn H.; Burkhauser, Richard V. (The Review of Economics and Statistics, 1989)
J. S. Butler, Kathryn H. Anderson, Richard V. Burkhauser, Work and Health after Retirement: A Competing Risks Model with Semiparametric Unobserved Heterogeneity, The Review of Economics and Statistics, Vol. 71, No. 1 (Feb., 1989), pp. 46-53